Project Performance Evaluation Using EVA Technique: Kotay Bridge Construction Project on Kayto River in Afghanistan - UĞURAL, MEHMET NURETTİN; BURGAN, HALİL İBRAHİM (University of Osijek, 2021)
The objective of the study is the assessment of an operating bridge project in terms of its performance by the evaluate project performance (EVA) technique. To apply the EVA technique, cost and schedule baselines and an update record of performed work with spent money is prepared for the project. The data is taken directly from site office of the project. Kotay bridge construction project is selected for case study. Project tracking is achieved by taking EVA technique to assess the Kotay bridge construction project performance in the last five months, and to find out the cost and time overruns if they exist. The Estimation at Completion (EAC) and To-Complete Performance Index (TCPI) are found as well to know how efficiently are used the remaining financial resources. The study revealed that CPI and SPI are both less than 1.0, which means that the project could not be performed well. Cost & time overruns are clearly indicated as well.
Keywords: Bridge Project; Earned Value Analysis (EVA); Kotay Bridge; Project Performance Evaluation; River